The Effectiveness of tv commercial ads on bullying / Nur Hanis Syafi Abdul Halim & Anwar Fikri Abdullah - Nur Hanis Syafi, Abdul Halim; Anwar Fikri, Abdullah (Universiti Teknologi MARA, Perak, 2018)
Bullying activities are not only occurring among school students, but also among the university students and workers too. Bullying has become a major disciplinary problem now. In order to solve this problem, the government must assign certain agencies to conduct awareness programs on the bullying symptoms to help parents and communities to deal with the issue more effectively. The purpose of this study is to deliberate upon the impacts of TV Commercial advertising on bullying to people and to identify those critical impacts which lead to behavioral disorder to people. This paper will explain on how to create an effective TV Commercial ads to attract the awareness of the people by using the elements and principles of TV Commercial such as characters, storyline and cinema graphics that help the audience know the moral value of the story. To reach the purpose, the research questions are focused on people’s opinion about the TV Commercial on bullying. Using this method might give the result to us about people opinion the impact of this TV Commercial ads.